Aspectos linguísticos pertinentes a educação escolar indígena no estado do Rio de Janeiro - Antunes, Suelen da Fonseca (2019)
Indigenous school education in the State of Rio de Janeiro has been imposed on native peoples since the beginning of colonization, to catechize and civilize them. However, consistent with their cosmologies and orality, the remaining peoples, mainly Mbyá Guarani, maintained their own way of education. Despite the indigenous linguistic losses due to educational forms that did not respect their diversity, grammar and memory, privileging only the teaching of Portuguese written models and external to their culture. These native peoples used strategies to live, reproduce, recreate and readapt their native language. Over the centuries. Currently, there is a bilingual education method of schools in the villages, through practices that seek in memory, in writing, in archiving and orality, in ancestral knowledge and in teaching the affirmative actions of the mother tongue of their ethnic identities. Public educational institutions and museums assist in practices that help in the composition and recomposition of collections for indigenous and non indigenous communities in Brazil and America in general to have access. The work is divided into six parts. In the first part, I introduce the Guarani people, especially the Mbyá, from the pre-colonial context to the present day. In this section, I show how 21st century indigenous school education is related and the concept of formal and oral school. In the second chapter, I describe the Guarani way of being. In the third part, I take a theoretical approach, based on the concepts of researchers on Indigenous Education in Brazil, Serafim Leite "History of the Company of Jesus in Brazil", 16th century volumes and the Travel Reports to Rio Negro by Gonçalves Dias in the 19th century and Indigenous Education in the 20th century. In the fourth part, I describe the Guarani Tava Mirim Extension Room and class attendance, belonging to the Guarani Karai Kuery Renda State Indigenous College. In the fifth part, I read the theoretical axes on Discourse Analysis. In the sixth part, I comment on the official Portuguese language curriculum used in the State Schools of Rio de Janeiro, curricular activities and their relationship with the indigenous bilingual school. In this section, I also discuss the convergences and divergences in the activities carried out by bilingual students in Guarani Mbyá and Brazilian Portuguese. I conclude with considerations on linguistic aspects in the analysis and description of reflective students' productions in their own ideological, discursive and linguistic knowledge.